Spinal 'flip‐flop' effect in anorexia nervosa: A case report. Issue 4 (9th February 2020) - Varotto, Alessia; Vitale, Valerio; Mansour, Mariam; Di Pascoli, Lorenza; Iannucci, Giuseppe
Summary: Anorexia nervosa is a psychiatric eating disorder related to malnutrition and consequent altered metabolism. A 48‐year‐old female with a history of anorexia in the last 2 years referred to our hospital with spinal pain. She underwent spinal X‐ray and magnetic resonance imaging (MRI) showing multiple vertebral collapses in dorsal and lumbar spine with inversion of normal bone marrow and soft tissue signal in T1‐weighted and STIR images. We describe this case of spinal 'flip‐flop' phenomenon, underlining how what seems a technical failure is actually a specific imaging pattern related to the clinical context.